Интеллектуальные игры: сборник / Е. Гик; Е. Пик - Гик Евгений (АСТ, 2005)
Экземпляры: (20181023) / Инвентарный номер: 41757 / Цена: 64.79 / Сис.шифр: 77.05 / Авт.знак: Г46 / ГРНТИ: 13.21.08 / ББК: 77.056